A broad review about face recognition – feature extraction and recognition techniques. (September 2015) - Sharma, R.; Patterh, M. S.
<x content-type="archive" xml:space="preserve">Abstract</x> Face recognition (FR) throws open a vast horizon of challenging tasks in the arena of facial image processing applications and computer visualisation, and hence has riveted keen interest during the last few years on account of its versatile applications in numerous spheres. Creating a useful facial design from initial face images is a very important gradient for victorious facial expression detection. Here, we furnish a report of several feature extraction and recognition methods which find themselves employed in the method of FR. The major aim of this survey is to assess the diverse FR methods according to their feature extraction and recognition techniques. From the analysis, we come to know about the feature extraction and recognition methods which have been elegant utilised in the FR procedure. They also vividly establish the technique which has performed excellently yielding superior FR precision by detecting face images more exactly. Moreover our study draws a concise picture of the feature extraction and recognition techniques and acts as a lodestar to the incoming intriguing investigators intending to increase their information about this innovative technique.